321 Effect of GxE on Breeding Cooperation Using Genomic Selection. (7th December 2018) - Cao, L
Abstract: Global selection of breeding livestock is becoming more and more frequent at this moment, especially in dairy cattle industry, which makes the interaction of genotype by environment (G×E) a more important role in breeding decision-making than previously estimated. This study was carried out to test the effect of G×E on the cooperation between two environments using stochastic simulations. Considering genomic selection (GS), we simulated breeding schemes which involved two environments in discrete generations. G×E was measured by the genetic correlation of performances of goal trait(s) between two environments (rg). Regardless of heritability, the average results of 20 replicates showed that the cooperation occurred when rg ≥ 0.7, and the cooperation was not affected by G×E any longer when rg ≥ 0.9. Therefore, We inferred that a break-even rg at which the across-environment GS breeding strategy becomes superior to the isolated within-environment breeding strategy would fall into the range between 0.7 and 0.9. Furthermore, as G×E decreased, genetic gains of breeding schemes under the two environments increased, while inbreeding depressions became slower. Hence, in the era of GS, our findings indicated that breeders could consider breeding cooperation with other environments when genetic correlation of performances of the goal trait(s) with other environment is beyond 0.7.